2019
DOI: 10.3390/su11246990
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Prospects of Sustaining Donor-Funded Projects in Rural Cameroon

Abstract: For more than five decades, developing countries (including Cameroon) have been primary beneficiaries of donor-funded projects targeting many sectors, including agriculture and rural development. Cameroon’s rural landscape witnessed a series of project interventions which emphasized sustainability. Although research efforts have been directed towards understanding the planning, implementation and impacts of donor-funded projects, not enough scientific information exists on the determinants, challenges and pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Muluh, et al [4] pointed that the failure of government services could affect the veterinary health services. Other factors include poor housing, low soil fertility for forage production, and weak market chains for livestock and their products.…”
Section: Livestock Production In Communal Areas In Sub-saharanmentioning
confidence: 99%
See 4 more Smart Citations
“…Muluh, et al [4] pointed that the failure of government services could affect the veterinary health services. Other factors include poor housing, low soil fertility for forage production, and weak market chains for livestock and their products.…”
Section: Livestock Production In Communal Areas In Sub-saharanmentioning
confidence: 99%
“…It should be observed that different livestock species have different ways of managing them thus highlighting good stockman ship as a prerequisite of livestock production. Livestock production can be intensive or extensive [4]. The intensive production is characterized by smaller number of herd sizes (number of animal on the farm), sometimes characterized by limited use of high production technology.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations